Recherche et développement dans les universités américaines : quel rôle pour les pouvoirs publics ? - Taoufik Djebali (Revue LISA)
The dynamism of the American economy is strongly related to the involvement of the federal government in the areas of research and development. Although this involvement, which can be considered as a partnership, dates back to the 19th century, it should be noted that the genuine “social contract” relating the state to the university goes back to 1945, i.e. following the publication of Science: the EndlessFrontier, a report written by Vannevar Bush. The creation of NSF, NASA, NIH, and other institutions, aimed at promoting and financing academic research. Since then, research and innovation have been strongly related to the university. The latter, in its turn, depends on public money for its survival. Indeed, a considerable amount of money is channelled every year by the Departments of Defense, Energy, and Health to American universities. The commitment of the federal government in favor of R&D at the university is not only financial; it is also fiscal and legal. Thanks to these policies, American universities are regarded as models of performance, inventiveness and profitability. This article will try to evaluate the role of the Federal Government in the promotion of R&D in the public and private universities and will focus on the adaptation of the latter to globalization. Indeed, since the 1980s the American university has been the spearhead in ensuring technological innovation and even the economic hegemony of the UnitedStates.